Insights into laryngeal Castleman disease: A comprehensive scoping review with a case study focus - Natalie Weiss; Estephania Candelo; Margaret Bridges; Amy Rutt (Laryngoscope Investigative Otolaryngology)
Abstract Introduction Castleman disease (CD) refers to a heterogeneous group of lymphoproliferative disorders, which rarely involves the larynx. Our goal in this study is to elucidate the clinical presentation, diagnostic techniques, and treatment methods of laryngeal CD through a scoping review and the addition of a new case. Methods Due to limited existing literature, we employed a mixed methodology for review. First, we searched Google Scholar using terms related to laryngeal CD. Subsequently, we screened abstracts using Covidence, drawing from databases such as PubMed, Science Direct, ProQuest, and EMBASE. We shortlisted studies for data extraction, focusing on clinical presentations, diagnostics, and treatment methodologies. Finally, we described our additional case. Results Scoping review revealed five qualifying laryngeal CD articles. Presenting symptoms included dysphagia, hoarseness, and dyspnea. Diagnosis was always established through histopathologic analysis. Management included local excision or radiotherapy. In our additional case, a 71‐year‐old male with known CD presented with neck swelling, dysphagia, and dysphonia. Exam revealed lymphoid laryngeal and supraglottic hyperplasia and edema. Laryngeal symptoms improved with medical management of CD. Discussion Given the rarity of laryngeal CD, its identification and management can be a challenge. Practitioners should be aware of characteristic points in a CD patient's history, physical exam, imaging, and biopsies. Local excision of obstructive lymphoid tissue and radiation are the best‐supported therapies. This study aims to build toward improvements in accurate diagnosis and appropriate treatment for laryngeal CD.